The Role of Zoos in Biodiversity Conservation - Fatima, Naz (MARKHOR (The Journal of Zoology), 2024)
The term zoo refers to a variety of institutions that house wild or exotic animals. Zoos can develop effective conservation strategies for endangered species, conduct scientific study to improve animal husbandry, impacts of the living collection, and employ educational initiatives to promote human interaction, development, and behavioral change due to their wide global reach. The commitment to biodiversity conservation guides day-to-day operations at zoos globally Zoos, as organizations mostly deal with different aspects of conservation like practice, research and advocacy. Conservation practices include species reintroduction initiatives, captive breeding, species survival strategies, and the utilization of zoo revenue for conservation programs in the wild. Zoos offer captive breeding programs for endangered species to regulate genetic diversity and maintain their population. The key aspect in conservation is advocacy which contributes to public engagement, supports stewardship, raises awareness and initiates fundraising programs, ultimately leading to protective environment for all kinds of species. Zoos provide knowledge on animal conservation, care, and confinement by conducting research and developing methodologies in wildlife biology, animal behavior, health, and welfare.They also promote educational and research initiatives in collaboration with scientists interested in animal conservation and preservation and ecological diversity. They inspire visitors to develop a relationship with wildlife by allowing them to observe live animals. Public engagement can ensure public awareness by communicating importance of biodiversity and advocates wildlife conservation Zoos serve an important role in restoring population of threatened and endangered species, protecting their habitats, maintaining genetic diversity, and developing new strategies for species conservation. Animal breeding programs and reintroduction to the wild or natural habitat help preserving rare and endangered species. Every zoo accredited by AZA (Association of Zoos and Aquariums), partners with conservation organizations for collaborative research efforts towards species extinction. Biodiversity conservation is a complex target that involves the participation of various stakeholders. Herein, zoos collaborate with government and non- government institutes and other researchers in various projects. The future of modern zoos will be determined by their ability to meet sustainable societal and environmental standards. Their goals should emphasize conservation by focusing on scientific research. However, some zoos have been criticized for prioritizing entertainment over animal welfare, while others argue that keeping animals captive is unethical. Despite these challenges, zoos continue to play an important role in the management, health, welfare and conservation of biodiversity.